Antrocaryon micraster (A. Chev. And Guillaumin) stem bark extract demonstrated anti-malaria action and normalized hematological indices in Plasmodium berghei infested mice in the Rane’s test - Kumatia, E.K.; Ayertey, F.; Appiah-Opong, R.; Bolah, P.; Ehun, E.; Dabo, J. (Journal of Ethnopharmacology, 2021)
Ethnopharmacological relevance: Malaria is caused by infection with some species of Plasmodium parasite which leads to adverse alterations in physical and hematological features of infected persons and ultimately results in death. Antrocaryon micraster is used to treat malaria in Ghanaian traditional medicine. However, there is no scientific validation of its anti-malaria properties. The plant does not also have any chemical fingerprint or standardization parameters. Aim of the study: This study sought to evaluate the anti-malaria activity of standardized A. micraster stem bark extract (AMSBE) and its effect on mean survival time (MST) and body weight reduction of Plasmodium berghei infested mice. And to study the effect of treatment of AMSBE on hematological indices of the P. berghei infested mice in order to partly elucidate its anti-malarial mechanism of action. Materials and methods: Malaria was induced in female ICR mice by infecting them with 0.2 mL of blood (i.p.) containing 1.0 × 107 P. berghei-infested RBCs from a donor mouse and leaving them without treatment for 3 days. AMSBE or Lonart (standard control) was then orally administered at 50, 200 and 400 mg/kg or 10 mg/kg once daily for 4 consecutive days. The untreated control received sterile water. Malaria parasitemia reduction, antimalarial activity, mean change in body weight and MST of the parasitized mice were evaluated. Furthermore, changes in white blood cells (WBCs), red blood cells (RBCs), platelets count, hemoglobin (HGB), hematocrit (HCT) and mean corpuscular volume (MCV) were also determined in the healthy animals before infection as baseline and on days 3, 5 and 8 after infection by employing complete blood count. Standardization of AMSBE was achieved by quantification of its constituents and chemical fingerprint analysis using UHPLC-MS. Results: Administration of AMSBE, standardized to 41.51% saponins and 234.960 ± 0.026 mg/g of GAE phenolics, produced significant (P < 0.05) reduction of parasitemia development, maximum anti-malaria activity of 46.01% (comparable to 32.53% produced by Lonart) and significantly (P < 0.05) increased body weight and MST of P. berghei infected mice compared to the untreated control. Moreover, there were significant (P > 0.05) elevation in WBCs, RBCs, HGB, HCT and platelets in the parasitized-AMSBE (especially at 400 mg/kg p.o.) treated mice compared to their baseline values. Whereas, the non-treated parasitized control recorded significant reduction (P < 0.05) in all the above-mentioned parameters compared to its baseline values. The UHPLC-MS fingerprint of AMSBE revealed four compounds with their retention times, percentage composition in their chromatograms and m/z of the molecular ions and fragments in the spectra. Conclusions: These results show that A. micraster stem bark possessed significant anti-malaria effect and also has the ability to abolish body weight loss, leucopenia, anemia and thrombocytopenia in P. berghei infected mice leading to prolonged life span. The UHPLC-MS fingerprint developed for AMSBE can be used for rapid authentication and standardization of A. micraster specimens and herbal preparations produced from its hydroethanolic stem bark extract to ensure consistent biological activity. The results justify A. micraster’s use as anti-malaria agent.
Research Article
Keywords: Malaria; Anemia; Leucopenia; Thrombocytopenia; Saponins; Phenolic compounds; Anacardiaceae; Chemical fingerprint analysis